ANALYSIS OF ENTERPRISE PROFITABILITY AND INFLUENCER FACTORS - Ismaylov Kuatbay Sarsenbaevich (Western European Studies, 2025)
The scientific article raises the problem of increasing the profitability of an enterprise. Using metnods for determining profitabilities, the level of profitabilities of the enterprise you are identified. Recommendations and proposals were also developed to increase the level of profitability.
Keywords: enterprise; net profit; gross profit; fixed assets